Effects of Maternal Empowerment Program on Stress, Anxiety, Depression and Parenting Confidence in Mothers of Preterm Infants in the Neonatal Intensive Care Unit - Yeonghee Shin; Jung Hee Lim; Gaeun Kim (Child Health Nursing Research, 2018)
Purpose: This study aimed to evaluate the effects of an empowerment program on maternal stress, anxiety, depression and parenting confidence. Methods: A total of 44 mothers of preterm infants were assigned into an experimental or a control group (n=22 each). The experimental group received the usual nursing care and 7 sessions of an empowerment program. The control group only received the usual care. The program was implemented from June to December, 2016 in the neonatal intensive care unit of K university-affiliated hospital in Daegu, Korea. The outcome variables measured were parental stress (PSS: NICU), anxiety (STAI), depression (CES-D) and parenting confidence. Data were analyzed using t-test or repeated measures ANOVA. Results: Scores for both parental stress (t=3.07 p=.004) and depression (F=3.76, p=.26) were significantly lower in the experimental group than in the control group. However, there were no significant differences in anxiety between the groups (F=0.79, p=.505). Parenting confidence scores (F=9.05, p=.001) were significantly higher in the experimental group than in the control group. Conclusion: A maternal empowerment program can be an effective means of reducing parental stress and depression as well as enhancing parenting confidence, for mothers of preterm infants.